Green Human Resource Management Practices and Environmental Performance in Ghana: The Role of Green Innovation - Ahakwa, Isaac; Yang, Jingzhao; Agba Tackie, Evelyn; Asamany, Mercy (SEISENSE Journal of Management, 2021)
Purpose- Protecting the natural environment and its wealth for future generations has become an essential topic for policymakers and executives. This study seeks to examine the impact of green Human Resource Management practices through green innovation on the environmental performance of small and medium-sized manufacturing enterprises in Ghana. Design/Methodology- Through simple random probability sampling, data were obtained from three hundred (300) business owners and employees from ten (10) small and medium-sized manufacturing enterprises in the Greater Accra Region of Ghana. However, two hundred and ninety-four (294) accurate responses were used in the analysis due to incomplete and missing figures. Data were analyzed using partial least squared based on Structural Equation Modeling (SEM). Findings- The studied data met internal consistency reliability, convergent, and discriminant validity from the results, and also, there was no multicollinearity issue in the study model. The findings revealed that green Human Resource Management practices directly and significantly influence environmental performance. Furthermore, green innovation partially mediated the influence of green Human Resource Management practices on environmental performance. Green compensation through green innovation has the most incredible impact on environmental performance and was statistically significant at p< 0.01. Practical Implications- This finding provides valuable suggestions for policymakers, emerging and existing organizations, particularly manufacturing firms, to encourage environmentally-friendly activities and produce goods and processes through a successful incentive scheme, thus increasing customer loyalty.